University proceedings. Volga region. Humanities - V.P. Mitrofanov (Известия высших учебных заведений. Поволжский регион: Гуманитарные науки)
Background. In the light of the discourse in modern historiography about abso-lutism, this problem deserves special study for a better understanding of the functioning of the institutions of royal power in Tudor England in the conduct of both domestic policy in general and agricultural policy in particular. Involving sources of state origin from this pe-riod will make it possible to identify the degree of violation of laws to limit enclosures and determine the effectiveness of royal commissions to restore peasant farms destroyed by landlords. Materials and methods. Using the comparative historical method of research, as well as the method of analysis and synthesis, observing the principle of historicism, various legal and narrative sources are analyzed, allowing us to trace the activities of the commis-sions to investigate enclosures and restore destroyed peasant farms, punish the gentry for the illegal conversion of arable land of peasants into pastures and eviction of themselves. Results. It was established that, thanks to the work of the commissions, the central govern-ment was well aware of the state of affairs in the agricultural sector and, in particular, with regard to the reduction of arable land, the number of peasants and farmers in a number of counties of the kingdom. However, the commissions’ data were incomplete due to the con-cealment of violators by local authorities. Despite the repressive measures taken, according to the results of the information collected by the commissions, against the gentry enclo-sures, not one of them was able to achieve the complete reconversion of pastures into arable land and the restoration of destroyed peasant farms. The position of local authorities was not always conducive to successful investigations by royal commissions. Conclusions. The organization of commissions and their work in the counties was an important instrument in the implementation of Tudor agricultural legislation. The work of the commissions to iden-tify illegal enclosures inevitably aroused dissatisfaction with the gentry, because contrary to the prevailing customary (manorial) law, the commissioners interfered in their relationships with the peasants. This could be one of the reasons for the fall of Cardinal Thomas Wolsey and the Duke of Somerset in the first half of the 16th century. The period of Elizabeth Tu-dor's reign was marked by a decline in the activity of investigating enclosures through commissions. This can be explained by some stabilization of the process of enclosures until the mid-1590s and increasingly widespread enclosures by agreement between peasants and lords of the manor, which made it difficult for commissions to identify illegal enclosures. However, parliament continued to pass new laws to limit enclosures.